Numerical evaluation on the effects of interceptor layout and blade heights for a prismatic planing hull. (October 2022) - Sahin, Omer Sinan; Kahramanoglu, Emre; Cakici, Ferdi
Highlights: The pressure distribution on the bottom of the hull and the wake profile change with the existence of the interceptor which leads to trim and resistance reduction. The interceptor is a useful device to drag reduction up to FnB =2.5 where the pressure forces are dominant. Higher blade height does not cause better hydrodynamic response especially when the beam Froude number is between 1.6 and 2.5. The 'best' interceptor layout and blade heights and hull trim angles in terms of total resistance are shown. Abstract: Planing hulls are exposed to effects such as trim and resistance that have a negative impact on their hydrodynamic performances. Interceptors are one of the systems to find solutions to reduce these negative effects. In this study, the effects of the interceptor layout and blade height on the hydrodynamic characteristics of a planing hull were investigated numerically, at varying speeds. The hydrodynamic behaviors of the interceptor at a selected case were also investigated in regular head waves. To reach this aim, a scaled prismatic planing hull form equipped with an interceptor which is suitable for planing vessels 4–10 m in length was selected for all analyses. The numerical study was performed by using the CFD (Computational Fluid Dynamics) approach which uses a finite volume method to discretize the RANS (Reynolds Averaged Navier Stokes) equations. The uncertainty of the numerical study was also performed to show the credibility of numerical results. According to the results of the current study, it is found that the most proper location of the interceptors for lower resistance is between the chine and the centerline of the selected planing hull. It is also understood that the effects of the blade height are directly related to the forward speed. Besides, the resistance values can be decreased by using interceptors up to FnB =2.5, while the presence of the interceptor has a negative effect on resistance after this speed regardless of the layout and selected blade height. In addition to this, the best interceptor blade heights for lower resistance at different forward speeds of the planing hull form were found for the tested cases. For the selected case, it is shown that interceptors are also useful in regular waves in terms of reducing dynamic trim, sinkage and resistance.